Gender-Based Development Discourse and Its Impact on Women Informal Workers in Yogyakarta - Budiman, Raihan Chaerani Putri; Rafeinia, Dhara Cita; Arintyas, Ameylia Puspita Rosa Dyah Ayu (Populasi, 2023)
Gender-based development in its implementation has challenges along with its characteristics, to be specific in efforts to achieve gender equality. Gender discrimination still occurs in Indonesia. It has become a culture in society which increasingly places women in a marginalized position. In this case, gender-based development is one of the main goals of the country’s development, as stated in the 2005-2025 RPJPN. Gender-appropriate roles need to be supported by efforts to optimize the role of women to bring about active participation in the development and eliminate inequality experienced by women. One way to realize gender-based development is through empowering women in informal work. The method used is qualitative, and data collection is carried out through semi-structured interviews and content analysis on media which that refer to the topic. The data is analyzed using the Miles and Huberman models with data reduction, data display, conclusions drawing/ verification, and given recommendations. The results of this study indicate that gender- based development in D.I. Yogyakarta has yet to succeed in reaching the understanding of the community, especially women informal workers.